PENGARUH HARGA, KEMASAN, RASA, VARIASI PRODUK, DAN KUALITAS PRODUK TERHADAP MINAT BELI (Studi Pada Usaha Gelamai Perentak Kecamatan Bangko Kabupaten Merangin) - Lara Parida; Arsa Arsa; Muhammad Subhan (CV. Aksara Global Akademia, 2023)
The growth of the food industry that occurred in Indonesia resulted in a high monthly expenditure category, the food industry can be said to be the market share leader with a larger percentage compared to other industries. The food industry is also developing in Bangko District, Merangin Regency. One of the foods that are also widely sold by the people of Bangko District, Merangin Regency, is gelamai perentak which is well known to people who pass through Bangko District, Merangin Regency. Perentak pretty much produced continuously by the community. There are several things that can be considered by the company such as product quality, and also product variety. It is suspected that this can help in increasing consumer buying interest. The purpose of this study was to determine the effect of price, packaging, and taste simultaneously on buying interest in the gelamai perentak business, Bangko District, Merangin Regency. In this study the method used is descriptive quantitative. The data sources of this research are primary data and secondary data with the research instruments used namely observation, questionnaires, and documentation. The results showed that the results of the t test for price, packaging, taste, and product quality had a positive and significant effect on purchase intention. While the product variation variable has no influence between product variation and buying interest. Based on the results of the F test with the help of calculations from the SPSS program, it can be seen that in the statistical F test it appears that the significance value of 0.000 is less than 0.05, namely 0.000 <0.05. So it can be concluded that the variable price (X1), packaging (X2), taste (X3), product variety (X4), and product quality (X5) together significantly influence purchase intention